Spatiotemporal characterization of cyclooxygenase pathway enzymes during vertebrate embryonic development - Leathers, Tess A.; Ramarapu, Raneesh; Rogers, Crystal D. (Developmental biology, 2025)
Vertebrate development is regulated by several complex well-characterized morphogen signaling pathways, transcription factors, and structural proteins, but less is known about the enzymatic pathways that regulate early development. We have identified that factors from the inflammation-mediating cyclooxygenase (COX) signaling pathway are expressed at early stages of development in avian embryos. Using Gallus gallus (chicken) as a research model, we characterized the spatiotemporal expression of a subset of genes and proteins in the COX pathway during early neural development stages. Specifically, here we show expression patterns of COX-1, COX-2, and microsomal prostaglandin E synthase-2 (mPGES-2) as well as the genes encoding these enzymes (PTGS1, PTGS2, and PTGES-2). Unique expression patterns of individual players within the COX pathway suggest that they may play non-canonical/non-traditional roles in the embryo compared to their roles in the adult. Future work should examine the function of the COX pathway in tissue specification and morphogenesis and determine if these expression patterns are conserved across species. [Display omitted] •COX pathway enzymes are present at the gene and protein level in embryonic tissues.•COX pathway transcripts are broadly expressed at low levels in chicken embryos.•COX1 protein is found in mitotic cells following ubiquitous gene expression.•COX2 ubiquitously expressed at the gene and protein level.•MPGES-2 gene and protein signal broad, with cell type-dependent subcellular localization.